Observation of photonic anomalous Floquet topological insulators - Maczewsky, Lukas J.; Zeuner, Julia M.; Nolte, Stefan; Szameit, Alexander (Nature Communications, 2017)
Topological insulators are a new class of materials that exhibit robust and scatter-free transport along their edges-independently of the fine details of the system and of the edge-due to topological protection. To classify the topological character of two-dimensional systems without additional symmetries, one commonly uses Chern numbers, as their sum computed from all bands below a specific bandgap is equal to the net number of chiral edge modes traversing this gap. However, this is strictly valid only in settings with static Hamiltonians. The Chern numbers do not give a full characterization of the topological properties of periodically driven systems. In our work, we implement a system where chiral edge modes exist although the Chern numbers of all bands are zero. We employ periodically driven photonic waveguide lattices and demonstrate topologically protected scatter-free edge transport in such anomalous Floquet topological insulators.
CRIS-Team Scopus Importer:2023-04-20